2020
DOI: 10.1002/csr.2059
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between integrated reporting and corporate environmental performance: A green trial

Abstract: Integrated reporting is a fairly recent phenomenon in the corporate reporting realm. Its dawn marks a new age of corporate reporting where financial and non‐financial information and their interrelation create an integrated and holistic approach for telling a value creation story. In tandem with this transformation, business sustainability in general and environmental performance, in particular, are also gaining prominence in the corporate landscape. This scholarly article investigates the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 103 publications
(158 reference statements)
4
63
1
Order By: Relevance
“…The authors also found no significant link between IR readability, IR tone bias, and CSR performance. Omran et al (2020) reported a positive impact of IR quality on environmental performance.…”
Section: Total Performance Measuresmentioning
confidence: 99%
“…The authors also found no significant link between IR readability, IR tone bias, and CSR performance. Omran et al (2020) reported a positive impact of IR quality on environmental performance.…”
Section: Total Performance Measuresmentioning
confidence: 99%
“…This change in companies and their commitment to the demands of interest groups has increased sustainability reports. Scholars who have decided to investigate the subject contribute to the scientific field in question [24].…”
Section: Discussionmentioning
confidence: 99%
“…[36,49] found that there is growing utilization of integrated reporting in South Africa and Sri Lanka, but both studies suggested that there are concerns with respect to the content and quality of these reports. On the one hand, [3,50,51] found evidence of a significant and positive effect between revealed information in integrated reporting and financial performance. On the other hand, [52], using data from 35 countries, found that revealed information by integrated reporting reduces agency costs and problems.…”
Section: Nowadaysmentioning
confidence: 99%